Feminist literary theory : a reader - Eagleton, Mary (Blackwell Publishers, 1996)
Is there a distinctive women's tradition in literature? Do women write differently from men? What does it mean to define a piece of writing as 'feminist'? Do women encounter particular problems in becoming writers? These are among the many questions addressed, debated and illuminated in this new edition of Mary Eagleton's classic reader in feminist literary theory. Radically revised and expanded from its original format, this second edition retains all the features that have made it indispensable to students and teachers of feminist literary theory across the world for a decade. The range of the collection remains unmatched by any similar volume, providing a superb point of entry into one of the broadest and most vibrant areas of contemporary theory. New material has been introduced throughout the reader, reflecting, in particular: the growing diversity of Black feminism, the continuing influence of 'French feminism' and the fundamental impact of postmodernism on feminism. New emphases have been introduced in every section, and a chapter covering postmodernist theories of subjectivity has been added. Fully indexed to make cross-referencing simple, this new edition is the perfect introduction to feminist literary theory today.